Analysis of Clinical Characteristics of 52 Patients with Uveitis before and after Vitrectomy and Factors Affecting Clinical Efficacy. (27th October 2021) - Liu, Qian; Zhou, Yinghong; Deng, Hongxia; Xiang, Xiaoxia; Chen, Chaohua; Wang, Chao; Huang, Ran
Abstract : Objective . To investigate the pre- and postsurgical clinical characteristics and clinical efficacy of patients with uveitis. Methods . The clinical data of patients with uveitis who underwent vitrectomy in our hospital from March 2019 to February 2021 were retrospectively analyzed. There were 52 cases of 64 eyes in total. The data on patient's gender, age, etiology, course of disease, anatomical classification, number of recurrences, changes in vision before and after surgery, changes in eye signs before and after surgery, and occurrence of postoperative complications were collected. The clinical features before and after vitrectomy were compared, and the influencing factors of clinical efficacy were analyzed. Results . The ocular signs of patients with uveitis after vitrectomy were significantly improved compared with before operation, and the difference was statistically significant (P < 0.05 ). The visual acuity after vitrectomy in patients with uveitis was significantly improved compared with that before operation, and the difference was statistically significant (P < 0.05 ). There was no significant difference in the surgical treatment of uveitis patients of different gender, age, and etiology (P > 0.05 ). There are significant differences in the clinical efficacy of vitrectomy in patients with different anatomical classifications. Among them, patients with panuveitis have the best clinical efficacy with vitrectomy and patients with posterior uveitis have the worst clinical efficacy with vitrectomy (P < 0.05 ). There is a significant difference in the clinical efficacy of vitrectomy in patients with recurrence times. The lower the number of recurrences, the better the clinical efficacy of vitrectomy in patients (P < 0.05 ). Conclusion . There are significant differences in the clinical signs of patients with uveitis before and after vitrectomy. Vitrectomy is effective in the treatment of uveitis. The type of anatomy and the number of recurrences are influencing factors for the clinical efficacy of vitrectomy. For patients with posterior uveitis, the surgical method should be carefully considered or a more reasonable treatment method should be selected, and for patients with uveitis with less recurrence, vitrectomy should be considered for active treatment.